Reconstructing Good University Governance Based on Islamic Values in Indonesian State Islamic Higher Education Institutions: A Systematic Literature Review (2020–2025) - Trian Hermawan; Fitriyana Fitriyana; Erlian Eka Damayanti; Idham Kholid (Institut Agama Islam An-Nawawi Purworejo, 2025)
Good University Governance (GUG) has emerged as a strategic issue in the management of Indonesian State Islamic Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Negeri—PTKIN), which operate under a dual mandate as public institutions and as higher education providers grounded in Islamic values. Bureaucratic reform, institutional autonomy, digital transformation of academic services, and increasing demands for public accountability have encouraged PTKIN to adopt contemporary governance principles. Nevertheless, recent scholarly work indicates that the incorporation of Islamic values into GUG practices remains largely normative and symbolic, and has yet to be operationally institutionalized within university governance systems. This study aims to systematically synthesize the development of research on Islamic values–based Good University Governance in PTKIN in Indonesia through a Systematic Literature Review (SLR). The review follows the PRISMA 2020 protocol and examines peer-reviewed publications from 2020 to 2025 retrieved from Scopus, SINTA, DOAJ, and reputable international academic publishers. A total of 42 articles were analyzed using qualitative thematic synthesis, supported by quality appraisal instruments from the Critical Appraisal Skills Programme (CASP) and the Joanna Briggs Institute. The synthesis reveals a substantial increase in GUG-related studies on PTKIN, with dominant emphases on transparency, accountability, participation, leadership roles, and information systems. Islamic values—namely amanah, al-‘adālah, mas’uliyyah, and maslahah—are consistently employed as normative justifications; however, they have not yet been reconstructed as institutional logics shaping measurable governance indicators and mechanisms. The literature is also predominantly characterized by descriptive qualitative studies and localized case analyses, resulting in notable conceptual and methodological gaps. This study contributes by proposing a conceptual model of Islamic values–based Good University Governance that integrates normative, structural, and practical dimensions, positioning Islamic values as the institutional logic underpinning governance practices within PTKIN.